Pilot-Scale Production of Lactobacillus Rhamnosus Atcc 7469 - Liew, Siew Ling (2004)
The present study was undertaken in view of the demand for probiotic products as a result of health awareness in consumers and the lack of information pertaining to industrial probiotic production processes. Response surface methodology (RSM) was used to optimize the culture medium for the growth of a probiotic bacterium, Lactobacillus rhamnosus ATCC 7469. The factors studied were yeast extract, glucose, vitamins concentrations and initial culture pH. A polynomial regression model with cubic and quartic terms was used for analysis of the experimental data. RSM was found to be effective in developing an analysis model, finding the optimum point of the factors and assessing the effects of the factors. It was found that the effects involving yeast extract, glucose, vitamins and pH on the growth of L. rhamnosus were significant, and the strongest effect was given by the yeast extract concentration. Estimated optimum conditions of the factors for the growth of L. rhamnosus were as follows : pH = 6.9; vitamin solution = 1.28% (v/v); glucose = 5.01% (w/v) and yeast extract = 6.0% (w/v). iii Further improvement of cell production was made by using a process optimization approach. The fermentation parameters investigated were aeration, mixing, pH, inoculum size and temperature. Cell production and viability were greatly influenced by the culture pH and temperature compared to other parameters such as agitation speed. The optimal culture conditions for the cultivation of L. rhamnosus in the 2-L stirred tank fermenter were as follows : mixing speed, 0.69 ms-1; pH, 6.9; temperature, 37°C and inoculum size of 5% (v/v) in facultative condition. Under this condition, final cell viability obtained was 1.61 x 1010 CFU mL-1, viable cell yield and productivity were 3.20 x 1011 CFU gglucose -1 and 1.33 x 109 CFU mL-1 h-1, respectively. Unstructured models based on Monod and Luedeking-Piret equations were developed and found to be suitable to describe the cell growth, lactic acid production and substrate consumption by L. rhamnosus in batch cultivation in a shake flask, 2- L, 10-L and 100-L stirred tank fermenters. Lactic acid production was a growthassociated and non-growth-associated (mixed) process. Scaling-up on the basis of constant impeller tip speed resulted in increasing mixing time as fermenter working volumes increased, but the mixing times were still within the critical acceptable range as fermentation performance was not significantly affected. Continuous cultivation was used in an attempt to further improve biomass production of L. rhamnosus. The maximum specific growth rate, μmax, and the Monod cell growth saturation coefficient, Ks, were estimated at 0.4 h-1 and 0.25 g L- 1. Maximum cell viability (1.29 x 1010 CFU mL-1) was achieved in the dilution rate (D) range of D = 0.28 h-1 to 0.35 h-1, while both maximum viable cell yield and iv productivity were achieved at D = 0.35 h-1. Continuous cultivation of L. rhamnosus at D = 0.35 h-1 gave 267% improvement in viable cell count productivity as compared to batch cultivations. Results obtained from exponentially fed-batch cultivation of L. rhamnosus at a D = 0.4 h-1 indicated that this mode of cultivation might be a good alternative for L. rhamnosus production as higher cell concentration and lower lactic acid production could be achieved when compared to batch and continuous cultivations